Медикаментозна та немедикаментозна корекція післяінсультних когнітивних порушень = Medical and non- medical correction of post-stroke cognitive impairments - Pulyk, O. R.; Stoyanov, O. M.; Gyryavets, M. W.; Vastyanov, R. S. (Journal of Education, Health and Sport, 2015)
Pulyk O R, Stoyanov O M, Gyryavets M W, Vastyanov R S. Медикаментозна та немедикаментозна корекція післяінсультних когнітивних порушень = Medical and non- medical correction of post-stroke cognitive impairments. Journal of Education, Health and Sport. 2015;5(5):109-116. ISSN 2391-8306. DOI 10.5281/zenodo.17455 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A109-116 https://pbn.nauka.gov.pl/works/559170 http://dx.doi.org/10.5281/zenodo.17455 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. УДК 616.89-008.434.5-06:616.831-005.4-085.21 МЕДИКАМЕНТОЗНА ТА НЕМЕДИКАМЕНТОЗНА КОРЕКЦІЯ ПІСЛЯІНСУЛЬТНИХ КОГНІТИВНИХ ПОРУШЕНЬ MEDICAL AND NON- MEDICAL CORRECTION OF POST-STROKE COGNITIVE IMPAIRMENTS О. Р. Пулик, О. М. Стоянов*, М. В. Гирявець, Р. С. Вастьянов* O R Pulyk, O M Stoyanov*, M W Gyryavets, R S Vastyanov* Ужгородський національний університет; *Одеський національний медичний університет Uzhgorod National University; *Odessa National Medical University Summary. The study involved 86 patients with symptoms of post-stroke cognitive impairments using nootropics – pramiracetam and fenibut and physiotherapy method – magnetic stimulation. The efficiency of both neuroprotective drugs in restoring of executive functions was proved, pramiracetam turned out to be efficient when restoring MMSE score, magnetic therapy – in restoring memory. Keywords: stroke, cognitive impairments, nootropics, magnetic therapy. Резюме. Проведено корекцію когнітивних порушень після перенесеного мозкового інсульту із застосуванням ноотропних препаратів – прамірацетаму та фенібуту, а також фізіотерапевтичного методу – магнітостимуляція 86 пацієнтам. Встановлено ефективність обох ноотропних препаратів при відновленні виконавчих функцій, препарату прамірацетам у відновленні показників шкали MMSE та магнітотерапії при відновленні пам’яті. Ключові слова: мозковий інсульт, порушення когнітивних функцій, ноотропні препарати, магнітотерапія. Резюме. МЕДИКАМЕНТОЗНАЯ И НЕМЕДИКАМЕНТОЗНАЯ КОРРЕКЦИЯ ПОСТИНСУЛЬТНЫХ КОГНИТИВНЫХ НАРУШЕНИЙ. Пулык А. Р., *Стоянов А. Н., Гирявец М. В., *Вастьянов Р. С. Проведена коррекция когнитивных нарушений у 86 пациентов после перенесенного мозгового инсульта с использованием ноотропных препаратов – прамирацетама и фенибута, а также физиотерапевтического метода – магнитостимуляция. Установлена эффективность обоих ноотропных препаратов при восстановлении исполнительных функций, препарата прамирацетам при восстановлении показателей шкалы MMSE и магнитотерапии при восстановлении памяти. Ключевые слова: мозговой инсульт, нарушение когнитивных функций, ноотропные препараты, магнитотерапия.